(untitled) (Sciences et Technologies pour l’Agriculture Durable, 2026)
Agro-morphological characterization is essential for providing relevant information to breeding programs. This study aimed to characterize 61 rainfed-lowland rice lines and identify those with superior drought tolerance using 06 qualitative and 04 quantitative traits. The trial was conducted on the AfricaRice experimental site in Sowé (Municipality of Glazoue), following an Alpha-lattice design with three replications. Multiple Correspondence Factorial Analysis followed by hierarchical clustering based on the qualitative traits revealed limited variability but identified class 1 as the most drought-tolerant. For quantitative traits, analysis of variance showed highly significant differences (P < 0.001). Hierarchical clustering based on principal component analysis grouped the lines into three homogeneous and distinct classes (P < 0.001), highlighting considerable phenotypic variation for traits such as emergence percentage, tillering at 30 and 60 days after sowing (DAS), and flowering date. Lines in class 2 (24 lines) were characterized by moderate tillering and a relatively short cycle (100.7 ± 1.26 DAS), while those in class 3 (23 lines) showed high tillering (1.7 and 17.9 tillers per plant at 30 and 60 DAS, respectively) and high emergence percentage. A the end of the study, the interspecific lines WAB2104-WAC4-1-TGR2-WAT3-1,WAB2104-WAC5-2-TGR1-WAT8-3b, and WAB2152-WAT13-1-2-TGR1 exhibited early flowering combined with superior drought tolerance. These findings provide valuable insights for the selection of drought-tolerant rice lines and highlight morphological and physiological traits associated with better adaptation to abiotic stress.